Bioactive Compounds in Nest-Associated Bacteria Termites and Their Bioactivity as Antivibrio in Aquaculture Industry - Dwinhoven, Ifhan; Amalia, Tiara; Haerunnisa, Siska; Nurhatijah; Abu Bakar, Khalil; Rani (International Journal of Applied Biology, 2023)
Abstract Vibriosis is a major problem in aquaculture that causes large numbers and rapid mortality of fish. Vibriosis treatment is still limited to the same antibiotics in humans and animals. This study aims to obtain bacterial isolates from termite nests that are antivibrio and determine the profile of the antivibrio bioactive compounds. Bacterial isolates were obtained from three types of termite nests. All isolates were cultured on ISP media and then characterized and conducted bioassay tests against Vibrio alginolyticus and Vibrio harveyi. Secondary metabolite fermentation products from selected bacterial isolates were extracted using ethyl acetate and detection of bioactive compounds by Thin Layer Chromatography (TLC) method. The isolation results obtained 15 isolates, 10 Gram-positive bacteria namely isolates SR1, SR2, SR8, SR9, RE2, RE3, RE5, SE1, SE4, SE6 while the other 5 isolates are Gram-negative bacteria. Antivibrio screening obtained 7 isolates that have antivibrio activity. The strongest antivibrio activity is SE1, which was able to inhibit the growth of V. alginolyticus bacteria with an inhibition zone of 3.5 cm and V. harveyi with an inhibition zone value of 4 cm and was also positive for catalase.  TLC showed that SE1 contained peptide compounds with purple color changes after dyeing using ninhydrin.